Reconstruction from cone integral transforms. (20th September 2017) - Palamodov, Victor
Abstract: The paper contains new reconstruction formulas for a function on 3D space from data of its cone integrals with fixed opening and integrable weight. In the case of cone integrals with the (non integrable) weight modelling photometric law, a reconstruction is obtained for the non redundant data of cones with the apex running on a curve.